Hakikat Guru dan Pendidikan Islam - Putri Utami Istiqomah; ahmad rifai (TA'DIB: Jurnal Pendidikan Agama Islam, 2025)
Teachers in Islamic education play a fundamental role, not only as transmitters of knowledge (mu’allim), but also as moral and spiritual guides for students (murabbi and mursyid). The background of this research highlights the crucial role of teachers in Islamic education amidst modern challenges such as globalization, technological advancements, and the changing character of students influenced by social media. The aim of this study is to explore the essence of a teacher’s role in Islamic education and how they can integrate Islamic values into the education process amidst these challenges. The research utilizes a library research methodology by analyzing various literature on the concept of teachers in Islamic education and the challenges they face in the modern era. The findings indicate that teachers in Islamic education must be able to harmonize religious values with contemporary educational methods to effectively shape a generation that is morally upright, intellectually capable, and spiritually grounded. Keywords: Teacher, Islamic Education, Mu’allim, Murabbi, Globalization, Educational Challenges